Growth of GaN quantum dots using [(C2H5)4]Si by plasma assisted MOCVD - Arsyad, F. S.; Subagio, A.; Sutanto, H.; Arifin, P.; Budiman, M.; Barmawi, M.; Husien, I.; Zul Azhar, Zahid Jamal (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org